KELUARGA SAKINAH MENURUT PERSPEKTIF AL-QUR’AN - Bhakti, Putri Ayu Kirana; Taqiyuddin, Muhammad; Saputra, Hasep (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2020)
A sakinah family is the hope for Muslim believers. However, to create it is not an easy case due to the community's low knowledge of sakinah family so that this factor can disturb the household. For the sake of providing explanations concerning this problem, this library research seek to find out a depiction of the sakinah family concept in the perspective of Qur’an. This study draws the following conclusion: First, the Sakinah family of course becomes a dream for every human being because this greatly has an impact on the levels of calm and comfort in the household. Having a sakinah family is the main choice in a household. Sakinah family has a number of criteria in the Qur'an, namely: Belief, responsibility, mutual forgiveness, and Mua'asyarah bil ma'ruf. Second, the factors contributing to the embodiment of sakinah family fall into the following: husband and wife must understand each other's rights, and they also accept each other's strengths or weaknesses.Keywords: Sakinah Family, Al-Quran Perspective